2018
DOI: 10.3390/toxins10070303
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Uremic Toxins on Cerebrovascular and Cognitive Disorders

Abstract: Individuals at all stages of chronic kidney disease (CKD) have a higher risk of developing cognitive disorders and dementia. Stroke is also highly prevalent in this population and is associated with a higher risk of neurological deterioration, in-hospital mortality, and poor functional outcomes. Evidence from in vitro studies and in vivo animal experiments suggests that accumulation of uremic toxins may contribute to the pathogenesis of stroke and amplify vascular damage, leading to cognitive disorders and dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 209 publications
(256 reference statements)
0
50
0
2
Order By: Relevance
“…Evidence from in vitro studies suggests that these UTs may display direct deleterious effects within brain microenvironment. Indeed, molecules such as Pi and IS were reported to favor leukocyte adhesion to endothelial cells from large vessels and to promote cerebral endothelial cells dysfunction, through increased oxidative stress 8 . Exposure of macrophages/microglia 20,3436 and astrocytes 23,24 to UTs amplified the release of inflammatory cytokines, oxidative stress and MMPs secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from in vitro studies suggests that these UTs may display direct deleterious effects within brain microenvironment. Indeed, molecules such as Pi and IS were reported to favor leukocyte adhesion to endothelial cells from large vessels and to promote cerebral endothelial cells dysfunction, through increased oxidative stress 8 . Exposure of macrophages/microglia 20,3436 and astrocytes 23,24 to UTs amplified the release of inflammatory cytokines, oxidative stress and MMPs secretion.…”
Section: Discussionmentioning
confidence: 99%
“…To date, little is known about the processes by which CKD worsens ischemic stroke. In addition, it has to be noted that most of our current knowledge in the field is based on data obtained from in vitro studies 8 . In a previous work, Yates et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that a slight decline in renal function manifests some degree of peripheral and central neurological complications due to a gradual increase in oxidative stress, inflammation, hemodynamic/vasoregulatory abnormalities, and uremic toxins in both humans and experimental models. 3135 Comorbid conditions like hypertension, diabetes, and atrial fibrillation in CKD patients also aggravates vascular complications (Figure 1). Even at an early stage of CKD, oxidative stress and low-grade inflammation make blood vessels and endothelium more vulnerable to even slight vascular shift, which in turn compromises the blood–brain barrier (BBB) integrity and facilitates infiltration of white blood cells (WBCs) and uptake of uremic toxins into central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an increase in Mg content in DFs has differential effects on the oxidative stress in IS-treated THP-1 cells depending on the dialysate used. renal function and the prevalence of cardiovascular events through altered leukocyte activation and intensified oxidative stress [3][4][5][6][7].Classically, UTs are divided into three categories: low-molecular-weight water-soluble solutes (<500 Da), middle-molecular-weight solutes (>500 Da), and protein-bound solutes [8]. These uremic toxins, represented by IS, is extremely toxic and difficult to eliminate by conventional dialysis; consequently, high IS levels may trigger oxidative-inflammatory stress, playing a key pathophysiologic role in CKD.…”
mentioning
confidence: 99%
“…Thus, an increase in Mg content in DFs has differential effects on the oxidative stress in IS-treated THP-1 cells depending on the dialysate used. renal function and the prevalence of cardiovascular events through altered leukocyte activation and intensified oxidative stress [3][4][5][6][7].…”
mentioning
confidence: 99%